Peran Penyuluh Agama Islam Melalui Majlis Taklim dalam Membina Perilaku Keagamaan Masyarakat di Desa Podosugih - Khabibah, Nur; Subhi, Muhamad Rifa'i (Taqorrub: Jurnal Bimbingan Konseling dan Dakwah, 2023)
This research aims to determine the role of Islamic religious instructors in fostering community religious behavior in Podosugih Village. This research uses a descriptive qualitative method, data collection was carried out by conducting research in the field and interviews with religious leaders in Podosugih Village. The role of Islamic religious instructors in fostering community religious behavior can be seen from holding activity programs in a place in order to shape and foster positive religious behavior and community personality. The implementation of Islamic religious counseling is the basis for implementing a broad series of outreach, with stages in transforming religious knowledge to the community. Factors supporting religious behavior are public awareness regarding understanding of religion, environmental factors, community spirit and educational factors. Furthermore, there are also inhibiting factors in fostering religious behavior, namely the lack of participation by the community, differences of opinion about religion, a sense of laziness within the community and a lack of parental support for their children.